Finite element modeling of seismic response of field fabricated liquefied natural gas (LNG) spherical storage vessels (2013)
All real physical structures behave dynamically when subjected to loads or displacements. This research paper, therefore, presents seismic response of field fabricated liquefied natural gas spherical storage vessels using finite element analysis. The seismic analysis procedure used represents a practical approach in quantifying the response of spherical storage vessel with its content when it is subjected to seismic loading. In the finite element method approach, six degrees of freedom per node is used for legs/column of the spherical storage tanks. Lumped mass procedure is employed to determine system mass matrix of the structure. Computer programme code is developed for the resulting matrix equation form finite element analysis of the structure using FORTRAN 90 programming language. The modeling of the seismic load utilizes the ground acceleration curve of a site. From the results of the modal analysis, the system is uncoupled thereby gives way to the application of Newmark’s method. Newmark’s method as one of the widely used time-step approach for the seismic response is applied. The developed programme coding is validated with analytical results (P > 0.5). It shows that the approach in this research work can be successfully used in determine the stability of large spherical storage vessels against seismic loadings when base acceleration spectral of the site are known. This approach gives better results than the static-force approach which gives conservative results. While the approach used in this research treats seismic loads as time event, static-force approach assumed that the full ground force due to seismic motion is applied instantaneously.